APLIKASI MODEL ARCS-V UNTUK MENGIDENTIFIKASI MOTIVASI MAHASISWA KEPERAWATAN MENGIKUTI PERKULIAHAN BLENDED LEARNING - Nazliansyah, Nazliansyah; Amiruddin, Amiruddin (Poltekkes Kemenkes Bandung, 2022)
Recently, most of the universities have implemented the online lecturing method in the virtual presentation as the education model. This method is very popular and effective due to flexibility and comprehensive-time. As the lecturing method, the online education models have negatif and positive impacts on the students. Likewise, the learning process has advantages and disadvantages. The objective of this study was to identify the correlation between blended learning implementation and nursing students' motivation in the learning process. The study design was a cross-sectional study and 112 nursing students participated in this study. The resulting study revealed that attention, relevance, and desire to learn were related to blended learning. On the other hand, gender, parent’s occupation, self-efficacy, and satisfaction were not related to the blended learning activity among nursing students. The results study can be referred to improve the education strategies in term of blended learning design program in increasing the attention, relevance, and volition lecturing process.